More Talent, More Leeway: Do Violence Against Women Arrests Really Hurt NFL Player Careers? - Sailofsky, Daniel (Violence against women, 2023)
This article examines whether arrests for an act of violence against women have a negative impact on National Football League (NFL) player careers and whether this impact has become more negative over time. Framed by criminological deterrence and conflict theories, I conduct a Bayesian multi-level negative binomial regression on a matched pairs sample of all 117 NFL players arrested for an act of violence against women between 2000 and 2019 (n = 234). Results show that the effect of an arrest on player careers is negligible, though it has become slightly more detrimental over time. Player value and performance are stronger predictors of post-arrest career trajectories, and average or better performance negates any detrimental impact of an arrest.